Systemic Antimicrobials Consumption and Expenditures in Departments of Surgery of Multi-Profile Hospitals in the Russian Federation and the Republic of Belarus: Results of Multicentre Pharmacoepidemiological Study - Yu. A. Belkova; S. A. Rachina; R. S. Kozlov; V. M. Mishchenko; R. A. Pavlyukov; A. I. Abubakirova; B. V. Berezhanskiy; E. V. Eliseeva; N. A. Zubareva; I. A. Karpov; I. A. Kopylova; Sh. Kh. Palyutin; et al. (Антибиотики и Химиотерапия)
The results of the systemic antimicrobials (AM) consumption and expenditures assessment in the departments of surgery of multiprofile hospitals in different regions of the Russian Federation and the Republic of Belarus in 2009-2010 based on retrospective collection and analysis of the data from the hospital expenditure notes using ATC/DDD methodology are presented. The average AM consumption and expenditure rates in the above mentioned departments varied from 24.9 DDD/100 bed-days to 61.7 DDD/100 bed-days depending on the department profile, with beta-lactams (cephalosporins and penicillins) share in the consumption being as high as 70-90%, followed by fluoroquinolones and aminoglycosides. Only 55-70% of the consumed AM belonged to the drugs of choice, whereas the improper AM consumption and expenditure rates amounted up to 10-18%. The study outputs can be used for the budget allocation and AM distribution improvement in the departments of surgery, as well as for the development and efficacy control of the local antimicrobial stewardship programs.